KAJIAN PENGARUH WARNA DAN JARAK LAMPU PENGAMAN TERHADAP HASIL RADIOGRAF - Setiyono, Setiyono; Azam, M.; Setiawati, Evi (BERKALA FISIKA, 2009)
The study of influence of distance, time and color for safety lamp filter variation to radiograph has been done.  The research used blue sensitive film and green sensitive, type -X ray, film. The research was conducted by illuminating film with safety lamp red, yellow, green and blue color filter. The type of filter was red acrylic riddle and glass which was layered in red, yellow, green and blue scot light. The variation of irradiating distance between safety lamp with film was 20 cm, 30 cm, 40 cm, 50 cm, 60 cm, 70 cm, 80 cm, 90 cm, 100 cm and variation of time is 10 second, 15 second, 20 second, 25 second, 30 second, 35 second, 40 second, 45 second, 50 second, 55 second, and 60 second. Respectualy measurement of irradiating resulted used measuring densitometer instrument. The result of research give an illustration that variation of distance, variation of time and color of safety lamp filter influence the radiograph.  The greater distance caused the fog result becomes smaller.  The longer time caused the fog result becomes bigger.  To red acrylic filter, the fog that resulted exceed the tolerance limit is more than 0,2, but for glass filter that layered red scot light is not more than tolerance limit. Keyword: Radiograph, Blue sensitive film, Green sensitive film, Fog, Scot light.